ANALYSIS OF VARIOUS FRONTAL BEAM MATERIAL AND SECTION USED IN PASSENGER VEHICLE - SHIVANI SHIVAJI ETHAPE; DR.R. R. RACHAYA; VIDYASAGAR BAJAJ (International Journal of Innovations in Engineering Research and Technology, 2021)
Bumpers play an important role in preventing the impact energy from being transferred to the automobile and passengers. Saving the impact energy in the bumper to be released in the environment reduces the damages of the automobile and passengers. The purpose of a crash analysis is to see how the car will behave in a frontal or sideways collision. Crashworthiness simulation is one typical area of application of Finite-Element Analysis (FEA). This is an area in which non-linear Finite Element simulations are particularly effective. The chassis frame forms the backbone of a heavy vehicle; its principle function is tosafely carry the maximum load for all the designed operating conditions. The frame should support the chassis components and the body